Histological study of resection arthroplasty with and without tendon ball interposition in dogs - Sardenberg, Trajano [UNESP]; Müller, Sérgio Swain [UNESP]; Pereira, Hamilton da Rosa [UNESP]; Coelho, Kunie Iabuki Rabello [UNESP] (SAGE Publications, 1999)
We studied an experimental model of resection arthroplasty with or without tendon ball interposition in the wrist of dogs. Animals were divided into two groups. Animals in group A were treated by resection of the os carpi radiale with interposition of a ball made from the tendon of the extensor carpi radialis and the group B underwent bone resection alone. Animals were assessed 1, 6, 12 and 24 weeks after operation. In all of them the wrist joint was stable and had good mobility, allowing walking supported by the operated limb. In both groups biological material filled the cavity created by bone resection. A progressive repair process resulted in fibroplasia with areas of fibrocartilaginous metaplasia. The tendon ball showed complete ischaemic necrosis at the end of the first week, which delayed the healing process. © 1999 The British Society for Surgery of the Hand.